Care and Cleaning of Maxillofacial Prostheses - Goiato, Marcelo Coelho [UNESP]; Rossatti Zucolotti, Bruna Carolina [UNESP]; Mancuso, Daniela Nardi [UNESP]; Santos, Daniela Micheline dos [UNESP]; Pellizzer, Eduardo Piza [UNESP]; Verri, Fellippo Ramos [UNESP] (Lippincott Williams & Wilkins, 2010)
Both the cleaning and care of the prosthesis are fundamental for maintaining its quality. Therefore, the aim of this study was to show the methods of cleaning and care the patient needs to take as regards the prosthesis and adjacent tissue, starting with correct instruction and training by the professional. It has been verified that among the materials for fabricating maxillofacial prostheses, silicone was considered the major retainer of microorganisms on its surface. Therefore, for cleaning prostheses, the use of water and neutral soap, as well as chlorhexidine, is recommended. As regards care of the adjacent tissues, it is recommended to remove the prosthesis before going to sleep, in addition to washing the prosthesis receptor tissues with water and neutral soap or with a mixture of hydrogen peroxide and water. Whereas for the mucosal surfaces of the ophthalmic cavity, cleaning with filtered and boiled water or physiological solution at least 3 times a day is recommended.
Keywords: Maxillofacial prosthesis; disinfection; inflammation